2008
DOI: 10.1080/10398560801958549
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Second-Generation Antipsychotics: The Experiences, Views and Monitoring Practices of Australian Child Psychiatrists

Abstract: Further research is required into the use, efficacy, side effects and monitoring of SGAs in children and adolescents, and there is a need to ensure that monitoring guidelines are implemented in clinical practice. This need is heightened by the likelihood that our data on clinicians' practice, which is based on their perceptions, may overestimate what actually occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 66 publications
(210 reference statements)
2
39
0
Order By: Relevance
“…Experts in health care improvement have emphasized the need to understand the problem, identify groups that should be targeted by efforts to improve adherence, and clarify barriers to implementation of adherence with guidelines. We identified three previous surveys of child psychiatrists that assessed monitoring of second-generation antipsychotics (3)(4)(5). In a U.S. survey of 334 child psychiatrists (published after the current survey was conducted), 53% of the respondents reported that patients were noncompliant with blood tests, but the study did not explore other barriers to monitoring (4).…”
mentioning
confidence: 96%
“…Experts in health care improvement have emphasized the need to understand the problem, identify groups that should be targeted by efforts to improve adherence, and clarify barriers to implementation of adherence with guidelines. We identified three previous surveys of child psychiatrists that assessed monitoring of second-generation antipsychotics (3)(4)(5). In a U.S. survey of 334 child psychiatrists (published after the current survey was conducted), 53% of the respondents reported that patients were noncompliant with blood tests, but the study did not explore other barriers to monitoring (4).…”
mentioning
confidence: 96%
“…A few, small-sample survey studies have been conducted with Canadian and Australian psychiatrists. These studies document a high level of awareness of potential metabolic and cardiac side effects associated the SGAs, but a limited use of monitoring practices (Doey et al 2007;Walter et al 2008;Morrato et al 2009). Little is known about SGA monitoring beliefs and patterns of United States-based child and adolescent psychiatrists, although recent research has shown that practice setting and physician attitudes influence off-label SGA use in children .…”
Section: Introductionmentioning
confidence: 99%
“…Risperidone is the most commonly prescribed antipsychotic drug in paediatric patients [4,12,13]. It has been repeatedly reported that risperidone is associated with much higher weight gain in children and adolescents than those in adults [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%